Circulating granulocyte colony-stimulating factor and functional outcome after ischemic stroke: an observational study. (2nd December 2021) - Wall, Alexander; Anger, Olof; Jood, Katarina; Blomstrand, Christian; Andreasson, Ulf; Blennow, Kaj; Zetterberg, Henrik; Isgaard, Jörgen; Jern, Christina; Åberg, N. David; Svensson, Johan
ABSTRACT: Objectives : While granulocyte colony-stimulating factor (G-CSF) has shown beneficial effects in experimental ischemic stroke (IS), these effects have not been reproduced clinically. Small-to-medium-sized observational studies have reported varying associations for G-CSF with stroke severity and post-stroke functional outcome, prompting their investigation in a larger study. Methods : Endogenous serum G-CSF (S-GCSF) was measured in the acute phase and after 3 months in patients with IS (N = 435; 36% females; mean age, 57 years) from the Sahlgrenska Academy Study on Ischemic Stroke (SAHLSIS). Stroke severity was scored according to the National Institutes of Health Stroke Scale (NIHSS), and the modified Rankin Scale (mRS) assessed functional outcomes at 3-month and 2-year post-stroke. Correlation and logistic regression analyses with confounder adjustments assessed the relationships. Results: The acute S-GCSF level was 23% higher than at 3-month post-stroke (p < 0.001). Acute G-CSF correlated weakly with stroke severity quintiles (r = 0.12, p = 0.013) and with high-sensitivity C-reactive protein (r = 0.29, p < 0.001). The association between S-GCSF (as quintiles, q) and poor functional outcome at 3 months (mRS 3–6; S-GCSF-q5 vs. S-GCSF-q1, age- and sex-adjusted odds ratio: 4.27, 95% confidence interval: 1.82–9.99; p = 0.001) withstood adjustment for cardiovascular risk factors and stroke subtype, but not additional correction for stroke severity. Post-stroke changes in S-GSCF and absolute 3-month S-GCSF were not associated with 3-month or 2-year functional outcomes. Discussion: Early post-stroke S-GCSF is increased in severe IS and associated with 3-month poor functional outcomes. The change in S-GCSF and the 3-month S-GCSF appear to be less-important, and S-GCSF likely reflects inflammation in large infarctions.